Humanitarian war in theory and practice : a case study of the NATO intervention in Kosovo - Godfrey, Owen Michael (2007)
This thesis aims to test and refine the theory of humanitarian war through the medium of a case study of the NATO intervention in Kosovo in 1999. Key research questions include: Is ‘humanitarian war’ a contradiction in terms? To what extent can military force be an appropriate and effective instrument for solving or averting humanitarian crises and ensuring respect for human rights? Is the concept, as some critics argue, too easily abused by powerful states seeking to justify wars fought for self-interested reasons? The thesis will look at the arguments of both proponents and critics of the concept of humanitarian war. The aim is to provide an immanent critique of the theory, judging it on its own terms; therefore when the arguments of critics are considered, the main emphasis will be on critics who come from within the liberal spectrum, rather than on realists or communitarians. It will examine the theory in terms of its three aspects- the jus ad bellum, jus in bello and jus post bellum- with the aim of taking a ‘longer view’ of intervention than is often the case in the existing literature, viewing it not as a discrete event but as part of a complex long-term process. The case of Kosovo was chosen as a recent intervention that has often been cited as a good example of a humanitarian war, and one which most proponents of the concept supported, at least in principle.